Functional analysis for probability and stochastic processes : an introduction - Bobrowski, Adam (Cambridge University Press, 2005)
This text is designed both for students of probability and stochastic processes, and for students of functional analysis. Numerous standard and non-standard examples and exercises make it suitable for both a textbook for a course as well as for self-study.